Pelestarian Olahraga Tradisional di Masyarakat Kabupaten Ogan Komering Ilir - Akbar, Rahmat; Riyoko, Endie; Iswana, Bayu (Institut Teknologi Pendidikan Indonesia, 2023)
The problems in this study are a) What are the supporting and inhibiting factors in the preservation of traditional games in the people of Ogan Komering Ilir Regency?; b) What are the government's efforts to preserve traditional sports activities in the people of Ogan Komering Ilir Regency? The objectives of this research are a) to find out what are the supporting and inhibiting factors in preserving traditional games in the people of Ogan Komering Ilir Regency?; b) To find out how the government's efforts to preservetraditional sports activities in the community of Ogan Komering Ilir district? The method used in this study is a qualitative approach with descriptive methods. Data collection techniques used in this study are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion.